The Effect of Artificial Aging on Al 6061/SiC Composite Produced by Thixoforming - Alhamidi, A. Ali; Sunardi, Sunardi; Satria, Dhimas; Yusuf, Yusvardi; Setiawan, Ipick; Verdana, Narendra Putra; Ula, Shofiatul (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Thixoforming improves material properties better than conventional methods through the formation of non-dendritic or rounded structures. This study aimed to optimize the mechanical properties of Al 6061/SiC composites by adding Mg as a wetting agent through stir casting, thixoforming, and artificial aging processes. The holding time during the artificial aging process was varied to investigate its effect on microstructure, hardness, and impact toughness. SEM analysis revealed a more uniform distribution of SiC particles with increasing holding time, indicating the effective formation of Mg2Si precipitates. The maximum hardness of 48.5 HRB and the highest impact toughness of 0.022 J/mm² were obtained at the longest holding time of 3 hours. This indicates that the formation of homogeneous Mg2Si precipitates during the artificial aging process significantly contributed to the improvement of the composite's mechanical properties.